Predicting outcomes of mechanically ventilated premature infants using respiratory severity score. (2nd December 2022) - Bhattacharjee, Indrani; Das, Anirudha; Collin, Marc; Aly, Hany
Abstract: Background: Extremely low birth weight (ELBW) infants have significant morbidities and higher mortality. The major morbidities are bronchopulmonary dysplasia (BPD), intraventricular hemorrhage (IVH) and retinopathy of prematurity (ROP). Release of proinflammatory cytokines has been implicated in the development of systemic inflammation that contributes to BPD aND ROP. Also, cumulative oxygen exposure in the first 3 days of life and use of mechanical ventilation was associated with 3-fold increase in severe IVH. Therefore, early ventilation and oxygenation may contribute significantly to morbidities in ELBW infants. Respiratory severity score (RSS), a product of Mean airway pressure (MAP) and FiO2, is a steady-state noninvasive assessment tool useful in infants to monitor the severity of respiratory failure. We used RSS, in the first 3 days of life of ELBW infants, to predict neonatal morbidities and mortality. Study design: In a single-center retrospective cohort study in an urban setting, convenience sampling of ELBW infants meeting the study criteria who were mechanically ventilated at birth for the first 3 days of life were included. Time-weighted average RSS was plotted on receiver-operating characteristic (ROC) curve in the first 3 days of life to predict outcomes. Sensitivity, specificity, positive predictive value, negative predictive value and likelihood ratios were calculated. Results: A total of 69 infants qualified for the study. RSS in the first 3 days significantly predicted the composite outcome of death, ROP, IVH or BPD with an area under the curve (AUC) of 0.82 ( p < 0.001). Individually, RSS predicted death, severe ROP and IVH with an AUC of 0.86, 0.77 and 0.71 respectively; but did not predict severe BPD (AUC 0.61). RSS was more sensitive and specific than each of its component; FiO2 and MAP. Weighted RSS in the first 3 days had high-negative predictive value of 98.1% for death between 7 days and 36 weeks, 94.6% for ROP and 91.7% for IVH. Conclusions: This study is the first to show that RSS in the first 3 days of life is a good predictor of composite neonatal outcomes: severe IVH, BPD, ROP, or mortality. Early RSS had a high positive predictive value for the composite outcome of morbidities/mortality and a high specificity for mortality, ROP, and IVH individually.